2019
DOI: 10.14295/cs.v10i1.1697
|View full text |Cite
|
Sign up to set email alerts
|

Correlations and path analysis in soybean progenies with resistance source to cyst nematode (race 3)

Abstract: Path analysis is an important study that slices the correlation coefficients between two variables to evaluate whether the relationship between them is of cause and effect. This study aimed to estimate the phenotypic and genotypic correlations between agronomic traits and perform a path analysis in order to identify variables for indirect selection aiming at a higher grain yield. Fourteen soybean F6 lines from the soybean breeding program of FCAV–UNESP, Jaboticabal, São Paulo, Brazil, were analyzed. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Among the 28 correlations analyzed, 20 presented genotypic magnitudes higher than phenotypic ones, especially when they showed negative values (Table 1). These results are desirable for selection, as the environmental effects have not outweighed the genetic effects (Dvorjak et al., 2019). For other variables, the genotypic correlation showing higher magnitudes than the phenotypic correlation, but there was no significant variation between both correlations in some associations.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 28 correlations analyzed, 20 presented genotypic magnitudes higher than phenotypic ones, especially when they showed negative values (Table 1). These results are desirable for selection, as the environmental effects have not outweighed the genetic effects (Dvorjak et al., 2019). For other variables, the genotypic correlation showing higher magnitudes than the phenotypic correlation, but there was no significant variation between both correlations in some associations.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the traits of HPI and NDM must be prioritized in the selection of superior soybean genotypes due to their direct and indirect effects on GY, which were very influential in all cultivation environments. Hence, indirect selection to increase GY is an efficient selection strategy to optimize the genetic gain of soybeans [ 40 ], even when considering contrasting environments.…”
Section: Resultsmentioning
confidence: 99%
“…Magashi et al, (2018) observed the association among some qualitative characters of different varieties of Soybean in the Sudan Savannah region. Dvorjak et al, (2019) conducted experiment to estimate the phenotypic and genotypic correlations between agronomic characters and perform a path analysis in order to identify growth components for indirect selection of high grain yielding variety of soybean crop. Patil and Deshmukh (1989) and Iqbal et al, (2003) also described the use of path analyses in blackgram breeding.…”
Section: Issn: 2319-7706 Volume 9 Number 3 (2020)mentioning
confidence: 99%